Green solvent for dissolving cellulose as well as preparation method and application of green solvent

By mixing guanidine organic alkali with acidic reagents at room temperature, a green solvent was prepared, which solved the problems of high costs and environmental pollution in existing cellulose dissolution technologies, and achieved efficient dissolution of cellulose, which was in line with sustainable development. concept.

CN119391010APending Publication Date: 2025-02-07BEIJING FORESTRY UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411511041.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing cellulose dissolution technology faces problems such as high cost, environmental pollution, low dissolution efficiency and equipment corrosion. Most ionic liquids have defects such as high cost, high viscosity, and strict synthesis conditions, which limit their industrial production. application.

Method used

By mixing guanidine organic alkali with acidic reagent at room temperature to form a homogeneous solution, and then heating and drying, a green solvent is prepared. The steps are concise and clear, cost-effective, and time is significantly reduced. Consumption and capital investment.

Benefits of technology

The green solvent demonstrates excellent solubility of cellulose that is widely available and inexpensive, broadens the source channels of raw materials, ensures the renewability of raw materials, reduces dependence on natural resources, and reduces environmental pollution. The core concept of sustainable development is highly consistent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391010A_ABST
    Figure CN119391010A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cellulose dissolution, and discloses a green solvent for dissolving cellulose and a preparation method and application thereof.The preparation method comprises the steps that guanidine organic alkali and an acid reagent are mixed to form a mixture, then the mixture is stirred and mixed at the room temperature until a homogeneous solution is formed, and the homogeneous solution is obtained; heating and drying the homogeneous solution to obtain a green solvent for dissolving cellulose; the preparation method provided by the invention has the advantages of simple and clear steps and low cost, time consumption and capital investment can be remarkably reduced, and dual optimization of efficiency and economy is realized. Experiments prove that the green solvent prepared by the method provided by the invention shows excellent dissolving capacity for widely available and cheap cellulose.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cellulose dissolution, and in particular to a green solvent for dissolving cellulose and a preparation method and application thereof. Background Art

[0002] Cellulose, as the most abundant natural polymer resource on earth, has the advantages of large reserves, renewable and biodegradable. Driven by the development of my country's modern circular economy system, high-performance cellulose products (such as high-strength artificial fibers, film materials, gel materials, etc.) have shown broad application prospects in the fields of textiles, aviation, environment, food, etc. Dissolution regeneration is the prerequisite for the high-value utilization of cellulose. However, the existence of a strong hydrogen bond network within and between cellulose molecules and the complex aggregate structure greatly hinder the solubility of cellulose in conventional solvents. Therefore, exploring efficient cellulose dissolution strategies to promote its industrial transformation and utilization is a key issue that needs to be urgently addressed in current research.

[0003] At present, researchers have successfully developed a variety of solvent systems, including NaOH / CS2 (viscosity method), N-methylmorpholine-N oxide (NMMO) aqueous solution (Lyocell method), sodium hydroxide / urea, alkyl ammonium hydroxide aqueous solution, lithium chloride / N, N-dimethylacetamide (LiCl / DMAc), etc. These solvent systems all show high solubility for cellulose, but they also face different challenges in the application process. Specifically, although the viscose method has a long history, its production process is cumbersome and lengthy, and it is accompanied by the discharge of a large amount of toxic gases and wastewater, which poses a significant threat to the environment. Although the Lyocell method uses green solvents and the preparation process is environmentally friendly, the high solvent cost and the potential explosive risk of amine oxide solvents in the cellulose regeneration process are problems to be solved in the application process. The sodium hydroxide / urea solvent system can only achieve the dissolution of low-polymerization cellulose, and it needs to maintain low temperature (-12°C) operating conditions, and the energy consumption is high. Although the alkyl ammonium hydroxide aqueous solution system has strong solubility, it itself has a certain corrosiveness, which will inevitably cause corrosion damage to the equipment. The cellulose solution prepared by the LiCl / DMAc system is prone to gelation and the solvent recovery is difficult, which limits its extensiveness and feasibility in practical applications.

[0004] In recent years, ionic liquids, as a new type of green solvent system, have the characteristics of high thermal stability, low volatility, green environmental protection, strong solubility and recyclability, opening up a new path for the transformation of biomass resources. Especially in the field of cellulose dissolution and regeneration, ionic liquids have shown great application potential. At present, researchers have used imidazole ([RRRIm] + ), pyridine ([RPi] + ), amine (NH4 + ) and other cations and halogens (X- ), tetrafluoroborate (BF4 - ), hexafluorophosphate (PF6 - ), trifluoromethanesulfonate (TfO - ) and other anions have been used to synthesize a variety of ionic liquids, such as 1-allyl-3-methylimidazolium chloride (AmimCl), 1-butyl-3-methylimidazolium chloride (BmimCl), etc. Although these ionic liquids have achieved remarkable results in cellulose dissolution, most of them have problems such as high cost, high viscosity, harsh synthesis conditions, and corrosiveness. In addition, ionic liquids with excellent solubility properties are often expensive, while ionic liquids with lower costs face challenges such as long dissolution time and severe cellulose degradation. These factors restrict their application in large-scale industrial production. It can be seen that it is very necessary to further develop a series of new ionic liquids with simple synthesis methods, low cost, low viscosity, green environmental protection, and excellent solubility properties, which is of great significance for the high-value utilization of cellulose resources. Summary of the invention

[0005] The present invention aims to solve at least one of the above technical problems in the prior art to a certain extent. To this end, the present invention provides a green solvent for dissolving cellulose and a preparation method thereof.

[0006] In order to achieve the above-mentioned objectives, the present invention provides, on the one hand, a method for preparing a green solvent for dissolving cellulose, the preparation method comprising mixing a guanidine organic base with an acidic reagent to form a mixture, then stirring the mixture at room temperature until a homogeneous solution is formed, and then heating and drying the homogeneous solution to obtain a green solvent for dissolving cellulose.

[0007] Preferably, the guanidine organic base is selected from at least one of 1,1,3,3-tetramethylguanidine, tetraethylguanidine, tetrapropylguanidine, 2-tert-butyl-1,1,3,3-tetramethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, chlorphenguanidine, metformin, polyhexamethylene biguanide, diphenylguanidine, proguanil, and sulfaguanidine.

[0008] Preferably, it is at least one of 1,1,3,3-tetramethylguanidine, 2-tert-butyl-1,1,3,3-tetramethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene.

[0009] Preferably, the acidic reagent is a monoprotic acid or a diprotic acid.

[0010] Preferably, the monoacid is selected from at least one of valeric acid, ethoxyacetic acid, 10-undecenoic acid, glycolic acid, aminoacetic acid, thioglycolic acid, formic acid, acetic acid, propionic acid, n-butyric acid, isobutyric acid, hexanoic acid, heptanoic acid, nonanoic acid, lauric acid, 3-mercaptopropionic acid, acrylic acid, lactic acid, pyruvic acid, 2-chloropropionic acid, 2-chloronicotinic acid, benzoic acid, p-hydroxybenzoic acid, phenylacrylic acid, α-methylacrylic acid, gluconic acid, cinnamic acid, alanine, leucine, isoleucine, valine, cystine, cysteine, methionine, threonine, serine, phenylalanine, tyrosine, tryptophan, proline, methionine, and hydroxyproline; more preferably, at least one of ethoxyacetic acid, formic acid, acetic acid, propionic acid, acrylic acid, and n-butyric acid.

[0011] The dibasic acid is selected from at least one of oxalic acid, malonic acid, succinic acid, maleic acid, adipic acid, pimelic acid, azelaic acid, sebacic acid, isophthalic acid, terephthalic acid, glutamic acid, aspartic acid, malic acid and tartaric acid.

[0012] Preferably, when the acidic reagent is a monoacid, the molar ratio of the guanidine organic base to the acidic reagent is (0.25-9):1; when the acidic reagent is a diacid, the molar ratio of the guanidine organic base to the acidic reagent is (1-2):1.

[0013] Preferably, the conditions for stirring the mixture at room temperature include: a stirring speed of 500 rpm, a stirring time of 4-10 min, and preferably a stirring time of 5 min.

[0014] Preferably, the conditions for heating and drying the homogeneous solution include: drying in a vacuum drying oven at a temperature of 90° C. for 6 hours.

[0015] Another aspect of the present invention provides a green solvent for dissolving cellulose prepared according to the above preparation method.

[0016] Another aspect of the present invention provides an application of the above-mentioned green solvent in dissolving cellulose, which includes adding a cellulose raw material to be dissolved into the green solvent, heating and continuously stirring until the cellulose raw material is dissolved to obtain a cellulose solution.

[0017] Preferably, the cellulose raw material is a mixture of one or more of wood dissolving pulp, cotton pulp, cotton linter pulp, wheat straw dissolving pulp, reed dissolving pulp, straw dissolving pulp, bamboo dissolving pulp and microcrystalline cellulose.

[0018] Preferably, in the cellulose solution, the mass percentage of the cellulose raw material is 2-12%.

[0019] Preferably, the heating temperature is 60-100°C, more preferably 80°C.

[0020] Preferably, the stirring speed is 300 rpm.

[0021] Preferably, the application further comprises recovering the solvent in the coagulation bath by rotary evaporation.

[0022] Through the above technical scheme, the preparation method provided by the present invention first mixes the guanidine organic base and the acidic reagent at room temperature, and applies continuous stirring until they are completely dissolved and present a uniform transparent phase, thereby obtaining a green solvent capable of dissolving cellulose. The above preparation method has the advantages of simple and clear steps and cost-effectiveness, which can significantly reduce time consumption and capital investment, and achieve dual optimization of efficiency and economy.

[0023] Experiments have shown that the green solvent prepared by the method provided by the present invention exhibits excellent solubility for cellulose, which is widely available and inexpensive. This feature not only broadens the source of raw materials and ensures the renewability of raw materials, but also greatly reduces the dependence on natural resources and effectively reduces environmental pollution, which is highly consistent with the core concept of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a graph showing the effect of 1,1,3,3-tetramethylguanidine-acetic acid ionic liquid on solvent conductivity at different molar ratios and temperatures.

[0025] Figure 2 It is a polarizing microscope picture of 4% bamboo dissolving pulp before and after being dissolved in ionic liquid in Example 11 of the present invention.

[0026] Figure 3 is a photograph of the regenerated cellulose film of the present invention.

[0027] Figure 4 is a photograph of the regenerated cellulose fiber of the present invention. DETAILED DESCRIPTION

[0028] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0029] The invention provides a method for preparing a green solvent for dissolving cellulose. The method comprises mixing a guanidine organic base with an acidic reagent to form a mixture, stirring the mixture at room temperature until a homogeneous solution is formed, and then heating and drying the homogeneous solution to obtain a green solvent for dissolving cellulose.

[0030] It can be seen that the preparation method provided by the present invention directly mixes the guanidine organic base with the acidic reagent at room temperature, and the steps are simple and clear, cost-effective, and significantly reduces time consumption and capital investment, achieving dual optimization of efficiency and economy. Furthermore, the inventors of the present application found that the green solvent prepared by the method provided by the present invention exhibits excellent solubility for cellulose, which is widely available and inexpensive. This feature not only broadens the source channels of raw materials and ensures the renewability of raw materials, but also greatly reduces the dependence on natural resources, effectively reduces environmental pollution, and is highly consistent with the core concept of sustainable development.

[0031] In the preparation method provided by the present invention, the guanidine organic base is selected from at least one of 1,1,3,3-tetramethylguanidine, tetraethylguanidine, tetrapropylguanidine, 2-tert-butyl-1,1,3,3-tetramethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, chlorphenguanidine, metformin, polyhexamethylene biguanide, diphenylguanidine, proguanil, and sulfaguanidine; more preferably, it is at least one of 1,1,3,3-tetramethylguanidine, 2-tert-butyl-1,1,3,3-tetramethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene.

[0032] In the preparation method provided by the present invention, the acidic reagent is a monoacid or a diacid. Wherein, the monoacid is selected from at least one of valeric acid, ethoxyacetic acid, 10-undecenoic acid, glycolic acid, aminoacetic acid, thioglycolic acid, formic acid, acetic acid, propionic acid, n-butyric acid, isobutyric acid, caproic acid, heptanoic acid, nonanoic acid, lauric acid, 3-mercaptopropionic acid, acrylic acid, lactic acid, pyruvic acid, 2-chloropropionic acid, 2-chloronicotinic acid, benzoic acid, p-hydroxybenzoic acid, phenylacrylic acid, α-methylacrylic acid, gluconic acid, cinnamic acid, alanine, leucine, isoleucine, valine, cystine, cysteine, methionine, threonine, serine, phenylalanine, tyrosine, tryptophan, proline, methionine, and hydroxyproline; more preferably, at least one of ethoxyacetic acid, formic acid, acetic acid, propionic acid, acrylic acid, and n-butyric acid.

[0033] The dibasic acid is selected from at least one of oxalic acid, malonic acid, succinic acid, maleic acid, adipic acid, pimelic acid, azelaic acid, sebacic acid, isophthalic acid, terephthalic acid, glutamic acid, aspartic acid, malic acid and tartaric acid.

[0034] The inventors of the present application have found in practice that if the amount of the acidic reagent is too much, the acidity of the mixture will be too strong, which will not only make it impossible to synthesize the ionic liquid, but also cause the cellulose raw material to inevitably degrade in the prepared solvent, resulting in a decrease in the yield of the product; if the amount of the acidic reagent is too little, it will be impossible to synthesize a green solvent that can effectively dissolve cellulose. For this reason, in the preparation method of the present invention, when the acidic reagent is a monobasic acid, the molar ratio of the guanidine organic base to the acidic reagent is (0.25-9):1; when the acidic reagent is a dibasic acid, the molar ratio of the guanidine organic base to the acidic reagent is (1-2):1.

[0035] In the preparation method provided by the present invention, the conditions for stirring the mixture at room temperature include: a stirring speed of 500 rpm, a stirring time of 4-10 min, and preferably a stirring time of 5 min.

[0036] In the preparation method provided by the present invention, the purpose of heating and drying the homogeneous solution is to remove unnecessary moisture. In a preferred embodiment, the conditions for heating and drying the homogeneous solution include: drying in a vacuum drying oven at a temperature of 90° C. for 6 hours.

[0037] The second aspect of the present invention provides a green solvent for dissolving cellulose prepared by the above preparation method.

[0038] The third aspect of the present invention provides an application of the above-mentioned green solvent in dissolving cellulose, which includes adding a cellulose raw material to be dissolved into the green solvent, heating and continuously stirring until the cellulose raw material is dissolved to obtain a cellulose solution.

[0039] In the specific reaction mechanism, the inventors found that in the process of heating and dissolving the cellulose raw material using the green solvent provided by the present invention, the carboxylic acid anions provided by the acidic reagent can form hydrogen bonds with the hydroxyl hydrogen atoms of C2 and C3 in the cellulose molecular chain, and the protons in the cations provided by the guanidine organic base mainly interact with the hydroxyl oxygen atoms of C6. These two components can synergistically destroy the strong hydrogen bond network of cellulose. In addition, as the heating temperature gradually increases, the solubility of the cellulose raw material in the green solvent provided by the present invention also increases. This phenomenon is attributed to the acceleration of the free ion transfer rate, which in turn promotes the swelling process of the cellulose raw material in the above-mentioned green solvent. Therefore, the green solvent provided by the present invention is like an efficient intermolecular scissors, which acts precisely on the cellulose chain and gives it ultra-high solubility. Finally, according to the technical solution provided by the present invention, the dissolved cellulose can be directly regenerated and converted into various types of cellulose materials through a coagulation bath, and no toxic or harmful substances are produced during the process.

[0040] In the present invention, the cellulose raw material can be any appropriate cellulose-rich material. In some embodiments of the present invention, the cellulose raw material is a mixture of one or more of wood dissolving pulp, cotton pulp, cotton linter pulp, wheat straw dissolving pulp, reed dissolving pulp, straw dissolving pulp, bamboo dissolving pulp, and microcrystalline cellulose.

[0041] It should be noted that when preparing raw material dissolving pulp, the selected cellulose raw material needs to undergo a series of processing to obtain raw material dissolving pulp. At this time, the raw material dissolving pulp contains α-cellulose with a content of ≥98%; when using dissolved cellulose to prepare regenerated cellulose film or regenerated cellulose fiber, microcrystalline cellulose, wood dissolving pulp, cotton pulp or bamboo dissolving pulp is generally preferred as raw material.

[0042] It should be noted that, in the present invention, the ratio of the cellulose raw material to the green solvent should be controlled within a certain range to ensure that the cellulose raw material can be reliably dissolved in the green solvent. In some embodiments of the present invention, the mass percentage of the cellulose raw material in the cellulose solution is 2-12%.

[0043] It is understandable that in the application described in the present invention, the purpose of heating and stirring is to improve the dissolution efficiency of cellulose. However, the inventors of the present application found that if the heating temperature is too high, a large amount of guanidine organic base in the green solvent will evaporate, resulting in a decrease in the green solvent's ability to dissolve cellulose, and insufficient heating temperature will cause the cellulose to fail to dissolve as quickly as possible. The inventors found that controlling the temperature conditions when dissolving cellulose at 60-100°C can not only achieve faster dissolution of cellulose, but also effectively avoid the evaporation of guanidine organic base. In particular, the heating temperature when dissolving cellulose is 80°C and the stirring speed is 300rpm, which is optimal.

[0044] Furthermore, in the application provided by the present invention, the solvent in the coagulation bath is recovered by rotary evaporation. It is understandable that the green solvent can be recycled by rotary evaporation, which not only significantly improves the production efficiency, but also effectively reduces the production cost, laying a solid foundation for realizing industrial production.

[0045] It should be noted that after the cellulose raw material is dissolved by the green solvent provided by the present invention, a variety of subsequent applications can be carried out, such as dissolving the cellulose raw material based on the green solvent provided by the present invention and further preparing regenerated cellulose film, or preparing regenerated cellulose fiber.

[0046] Specifically, the steps of dissolving the cellulose raw material based on the green solvent provided by the present invention and further preparing the regenerated cellulose film include:

[0047] S101, adding a cellulose raw material to the green solvent provided by the present invention, heating and dissolving under magnetic stirring conditions to obtain a transparent cellulose homogeneous solution;

[0048] S102, placing the homogeneous cellulose solution obtained in step S101 in an oven for static degassing treatment, then coating it on a smooth glass plate to form a film, and then placing the glass plate in a vacuum drying oven to make the homogeneous cellulose solution evenly leveled;

[0049] S103, placing the glass plate in step S102 into a coagulation bath, coagulating and regenerating at room temperature, washing the obtained film with deionized water for 3-4 times, and drying the film at room temperature to obtain a regenerated cellulose film.

[0050] Wherein, in step S101, the dissolution temperature of the cellulose raw material is 60-100°C, and the rotation speed of the magnetic stirring is 300 rpm; in the obtained cellulose homogeneous solution, the mass percentage concentration of the cellulose raw material is 2-12%, preferably 3-7%.

[0051] In step S102, the temperature of the degassing treatment in the oven is 60-90°C and the time is 1-12 hours.

[0052] The thickness of the film formed by knife coating the cellulose homogeneous solution on the glass plate is 0.2-0.8 mm, and the temperature of the vacuum drying oven is 60-100° C., preferably 80° C.

[0053] In step S103, the coagulation bath is selected from one of anhydrous ethanol, methanol, isopropanol, dimethyl sulfoxide, and acetone, and the immersion time of the coagulation bath is 1-24 hours.

[0054] The steps of dissolving the cellulose raw material based on the green solvent provided by the present invention and further preparing the regenerated cellulose fiber include:

[0055] S201, dissolving a cellulose raw material in the green solvent provided by the present invention to obtain a transparent cellulose homogeneous solution, and using the solution as a spinning solution;

[0056] S202, placing the spinning solution in an oven for static degassing, and then extruding it from the spinneret hole into a coagulation bath for regeneration to obtain primary fibers;

[0057] S203, stretching, drying, curling and winding the primary fibers to obtain regenerated cellulose fibers.

[0058] Wherein, in step S201, the mass percentage concentration of the cellulose raw material in the obtained cellulose homogeneous solution is 2-10%.

[0059] In step S202, the temperature of the degassing treatment in the oven is 50-90°C and the time is 1-3 hours.

[0060] In step S202, the spinning pressure is 0.6 MPa, the spinning temperature is 60-90°C, the spinning solution extrusion speed is 0.5-5 m / min, and the spinning method is wet spinning or dry-jet wet spinning.

[0061] The coagulation bath is at least one of anhydrous ethanol, acetone, methanol, isopropanol, dimethyl sulfoxide and acetone. The length of the coagulation bath is 0.5-2m, and the residence time of the spinning solution stream in the coagulation bath is 5-60min.

[0062] The green solvent for dissolving cellulose provided by the present invention is further described below through specific examples.

[0063] 1. Dissolved cellulose

[0064] Example 1

[0065] Take 24.19g 1,1,3,3-tetramethylguanidine and 5.40g acetic acid, stir mechanically at room temperature for 5min, and rotate at 400rpm to prepare 1,1,3,3-tetramethylguanidine-acetic acid ionic liquid with a molar ratio of 2.33. The obtained ionic liquid was dried in a vacuum drying oven at 90℃ for 6h. The viscosity of the ionic liquid measured at room temperature was 47.33mPa.s. The temperature was raised to 80℃, and the conductivity of the ionic liquid at 80℃ was measured to be 2376.60μS / cm. Weigh microcrystalline cellulose (DP=263) and add it to the above cellulose solvent, and continue stirring at 100℃ and 300rpm until it can no longer be dissolved. Analysis shows that the maximum solubility of microcrystalline cellulose is 14.61%.

[0066] Example 2

[0067] Take 17.28g 1,1,3,3-tetramethylguanidine and 9.01g acetic acid, stir mechanically at room temperature for 5min, speed 400rpm, prepare 1,1,3,3-tetramethylguanidine-acetic acid ionic liquid with a molar ratio of 1.00. The obtained ionic liquid is dried in a vacuum drying oven at a temperature of 90℃ for 6h. The viscosity of the ionic liquid measured at room temperature is 190.61mPa.s. The temperature is raised to 80℃, and the conductivity of the ionic liquid at 80℃ is measured to be 1627.80μS / cm. Weigh microcrystalline cellulose (DP=263) into the above cellulose solvent, continue stirring at 80℃ and 300rpm until it can no longer be dissolved. Analysis shows that the maximum solubility of microcrystalline cellulose is 11.22%.

[0068] Example 3

[0069] Take 20.73g 1,1,3,3-tetramethylguanidine and 7.21g acetic acid, stir mechanically at room temperature for 5min, and rotate at 400rpm to prepare a 1,1,3,3-tetramethylguanidine-acetic acid ionic liquid with a molar ratio of 1.5. The obtained ionic liquid was dried in a vacuum drying oven at 90°C for 6h. The viscosity of the ionic liquid measured at room temperature was 55.64mPa.s. The temperature was raised to 80°C, and the conductivity of the ionic liquid at 80°C was measured to be 1921.01μS / cm. Weigh bamboo dissolving pulp (DP=533) and add it to the above cellulose solvent, and continue stirring at 90°C and 300rpm until it can no longer be dissolved. Analysis shows that the maximum solubility of bamboo dissolving pulp is 9.56%.

[0070] Example 4

[0071] Weigh 24.19g 1,1,3,3-tetramethylguanidine and 6.49g acrylic acid, stir mechanically at room temperature for 5min, speed 400rpm, prepare 1,1,3,3-tetramethylguanidine-acrylic acid ionic liquid with a molar ratio of 2.33. The obtained ionic liquid was dried in a vacuum drying oven at a temperature of 90℃ for 6h. The viscosity of the ionic liquid measured at room temperature was 48.63mPa.s. The temperature was raised to 80℃, and the conductivity of the ionic liquid at 80℃ was measured to be 2271.32μS / cm. Weigh cotton pulp (DP=898) and add it to the above cellulose solvent, continue stirring at 100℃ and 300rpm until it can no longer be dissolved. Analysis shows that the maximum solubility of cotton pulp is 9.06%.

[0072] Example 5

[0073] Take 24.19g 1,1,3,3-tetramethylguanidine and 6.67g propionic acid, stir mechanically at room temperature for 5min, and rotate at 400rpm to prepare 1,1,3,3-tetramethylguanidine-propionic acid ionic liquid with a molar ratio of 2.33. The obtained ionic liquid was dried in a vacuum drying oven at 90℃ for 6h. The viscosity of the ionic liquid was measured to be 42.10mPa.s at room temperature. The temperature was raised to 80℃, and the conductivity of the ionic liquid at 80℃ was measured to be 1799.70μS / cm. Weigh the wood dissolving pulp (DP=797) and add it to the above cellulose solvent, and continue stirring at 100℃ and 300rpm until it can no longer be dissolved. Analysis shows that the maximum solubility of the wood dissolving pulp is 8.35%.

[0074] Example 6

[0075] Weigh 19.49g of 1,5,7-triazabicyclo[4.4.0]dec-5-ene and 5.43g of mercaptoacetic acid, stir mechanically at room temperature for 5min, and rotate at 400rpm to prepare a 1,5,7-triazabicyclo[4.4.0]dec-5-ene-thioglycolic acid ionic liquid with a molar ratio of 2.33. The obtained ionic liquid was dried in a vacuum drying oven at 90°C for 6h. The viscosity of the ionic liquid measured at room temperature was 198.15mPa.s. The temperature was raised to 80°C, and the conductivity of the ionic liquid at 80°C was measured to be 390.01μS / cm. Weigh wood dissolving pulp (DP=797) and add it to the above-mentioned cellulose solvent, and continue stirring at 80°C and 300rpm until it can no longer be dissolved. Analysis shows that the maximum solubility of wood dissolving pulp is 1.01%.

[0076] Example 7

[0077] Weigh 23.98g of 2-tert-butyl-1,1,3,3-tetramethylguanidine and 6.25g of ethoxyacetic acid, stir mechanically at room temperature for 5min, and rotate at 400rpm to prepare a 2-tert-butyl-1,1,3,3-tetramethylguanidine-ethoxyacetic acid ionic liquid with a molar ratio of 2.33. The obtained ionic liquid was dried in a vacuum drying oven at a temperature of 90°C for 6h. The viscosity of the ionic liquid measured at room temperature was 53.30mPa.s. The temperature was raised to 80°C, and the conductivity of the ionic liquid at 80°C was measured to be 1281.14μS / cm. Weigh bamboo dissolving pulp (DP=533) and add it to the above-mentioned cellulose solvent, and continue stirring at 100°C and 300rpm until it can no longer be dissolved. Analysis shows that the maximum solubility of bamboo dissolving pulp is 6.16%.

[0078] Example 8

[0079] Weigh 16.13g of 1,1,3,3-tetramethylguanidine and 7.28g of malonic acid, stir mechanically at room temperature for 5min, and rotate at 400rpm to prepare a 1,1,3,3-tetramethylguanidine-malonic acid ionic liquid with a molar ratio of 2.00. The obtained ionic liquid was dried in a vacuum drying oven at 90°C for 6h. The viscosity of the ionic liquid measured at room temperature was 75.64mPa.s. The temperature was raised to 80°C, and the conductivity of the ionic liquid at 80°C was measured to be 1021.01μS / cm. Weigh bamboo dissolving pulp (DP=533) and add it to the above-mentioned cellulose solvent, and continue stirring at 90°C and 300rpm until it can no longer be dissolved. Analysis shows that the maximum solubility of bamboo dissolving pulp is 3.56%.

[0080] Example 9

[0081] Weigh 24.19g 1,1,3,3-tetramethylguanidine and 10.99g benzoic acid, stir mechanically at room temperature for 5min, rotate at 400rpm, and prepare 1,1,3,3-tetramethylguanidine-benzoic acid ionic liquid with a molar ratio of 2.33. It was found that no ionic liquid was formed at room temperature. Weigh wood dissolving pulp (DP=797) and add it to the above cellulose solvent, and it was found that the ionic liquid could not dissolve the wood dissolving pulp.

[0082] Example 10

[0083] Weigh 16.21g 1,1,3,3-tetramethylguanidine and 11.06g 10-undecenoic acid, mechanically stir at room temperature for 5min, rotate at 400rpm, and prepare 1,1,3,3-tetramethylguanidine-10-undecenoic acid ionic liquid with a molar ratio of 2.33. The obtained ionic liquid was dried in a vacuum drying oven at a temperature of 90°C for 6h. The viscosity of the ionic liquid measured at room temperature was 213.86mPa.s. The temperature was raised to 80°C, and the conductivity of the ionic liquid at 80°C was measured to be 380.44μS / cm. Weigh bamboo dissolving pulp (DP=533) and add it to the above-mentioned cellulose solvent, and continue stirring at 100°C and 300rpm until it can no longer be dissolved. Analysis shows that the maximum solubility of bamboo dissolving pulp is 2.08%.

[0084] The parameters in the above embodiments 1-10 are summarized in Table 1.

[0085] Table 1

[0086]

[0087]

[0088] Wherein, “—” indicates that the green solvent was not prepared.

[0089] According to the method of the above embodiment, 1,1,3,3-tetramethylguanidine-acetic acid ionic liquid with a molar ratio of 1.00 to 9.00 was prepared, and its conductivity under different temperature conditions was tested. Figure 1As shown. It can be clearly seen from the above examples that the conductivity of the ionic liquid shows a trend of first increasing and then decreasing as the molar ratio increases. At the same time, the conductivity also increases significantly as the temperature increases. In particular, the conductivity reaches a maximum value when the molar ratio of the guanidine organic base / acidic reagent is 2.33. And this change trend is consistent with the change trend of the solubility of cellulose. It can be inferred that the interaction between the ionic liquid and the cellulose plays a key role in the dissolution process. As the temperature increases, the solvation degree of cellulose is enhanced, because the increase in temperature accelerates the migration rate of anions and cations in the ionic liquid, thereby promoting the dissolution of cellulose, so that its solubility increases with the increase in temperature. However, when the molar ratio is too high, the ionization of anions and cations in the ionic liquid will be inhibited, resulting in a decrease in the number of free ions, which in turn inhibits the dissolution of cellulose. On the other hand, as the molar ratio continues to increase, the viscosity of the ionic liquid shows a downward trend, which is conducive to increasing the migration rate of anions and cations, and plays a positive role in promoting the dissolution of cellulose. Therefore, when the molar ratio reaches a specific point of 2.33, the effects of the above two factors on cellulose dissolution reach a balance, at which time the solubility of cellulose reaches its maximum value.

[0090] It can also be clearly seen from the above examples 3 to 10 that the solubility of cellulose is greatly affected by the viscosity and type of the ionic liquid. Specifically, those low-viscosity ionic liquids show particularly significant advantages in the process of cellulose dissolution. As the temperature gradually increases, the free ion transmission rate in these low-viscosity ionic liquids is significantly accelerated, which not only greatly promotes the interaction between the ionic liquid and the cellulose molecules, but also enhances the swelling effect of cellulose in the ionic liquid. In this process, the carboxylic acid anions provided by the acidic reagent mainly form stable hydrogen bonds with the hydroxyl hydrogen atoms at the C2 and C3 positions on the cellulose chain. The protons in the cations provided by the guanidine organic base mainly interact with the hydroxyl oxygen atoms at the C6 position of the cellulose chain. It is this specific interaction mechanism that effectively destroys the original hydrogen bond network structure between cellulose molecules and realizes the dissolution of cellulose. Different types of anions and cations have different solubility for cellulose. Generally, the electron-withdrawing groups and bulky groups in the anionic structure are not conducive to the dissolution of cellulose, but the electron-donating groups promote the dissolution of cellulose.

[0091] 2. Preparation of regenerated cellulose products

[0092] Embodiment 11

[0093] Take 24.19g 1,1,3,3-tetramethylguanidine and 5.40g acetic acid, stir mechanically at room temperature for 5min, speed 400rpm, prepare 1,1,3,3-tetramethylguanidine-acetic acid ionic liquid with a molar ratio of 2.33. The obtained ionic liquid is dried in a vacuum drying oven at a temperature of 90℃ for 6h. Weigh 4% bamboo dissolving pulp (DP=533) and add it to the above cellulose solvent, heat at 300rpm, 90℃ for 2h until the bamboo dissolving pulp is completely dissolved. Polarized microscope photos before and after dissolution are shown as follows: Figure 2 After standing in an oven at 80°C for 1 hour to defoam, the film was scraped onto a glass plate that had been preheated in an oven at 80°C for 20 minutes, and then the glass plate was placed in a vacuum drying oven at 80°C to make the cellulose solution evenly leveled. The glass plate was placed in a coagulation bath of anhydrous ethanol, and coagulated and regenerated at room temperature. The obtained film was washed with deionized water for 3 to 4 times, and the regenerated film was placed at room temperature for 48 hours and then dried to obtain a regenerated cellulose film such as Figure 3 . Finally, the coagulation bath is recovered by rotary evaporation at 60°C. The regenerated film tensile test process is: the regenerated cellulose film is cut into a fixed size, placed in the two clamps of the Zwick / Roell tensile tester, so that the longitudinal axis of the regenerated cellulose film coincides with the center line of the upper and lower clamps, and the tensile tester is started until the film breaks; the tensile test shows that the film strength can reach 281MPa, which is higher than the conventional dissolution film strength. This is conducive to broadening the application field of the film and increasing the timeliness of the application.

[0094] Example 12

[0095] Take 24.19g of 1,1,3,3-tetramethylguanidine and 6.49g of acrylic acid, stir mechanically at room temperature for 5min, and rotate at 400rpm to prepare a 1,1,3,3-tetramethylguanidine-acrylic acid ionic liquid with a molar ratio of 2.33. The obtained ionic liquid was dried in a vacuum drying oven at a temperature of 90°C for 6h. Weigh 4% of wood dissolving pulp (DP=797) and add it to the above-mentioned cellulose solvent, heat at 300rpm and 80°C for 3h until the wood dissolving pulp is completely dissolved, and the obtained homogeneous solution is used as the spinning solution. After the spinning solution is allowed to stand and degas in an oven at 80°C for 1h, the above-mentioned spinning solution is extruded from the spinneret at a pressure of 0.5MPa, 80°C, and a speed of 0.5m / min to regenerate into anhydrous ethanol solution to obtain primary fibers. The primary cellulose fibers are stretched 1.1 times, dried at room temperature, and curled and wound to obtain regenerated cellulose fibers, such as Figure 4 Finally, the coagulation bath was recovered by rotary evaporation at 60°C. The regenerated cellulose fiber was cut into fixed lengths and placed in two clamps of a Zwick / Roell tensile tester, so that the longitudinal axis of the regenerated cellulose film coincided with the center line of the upper and lower clamps, and the tensile tester was started until the fiber broke; the tensile test showed that the dry tensile strength of the fiber was 2.51 cN / dtex.

[0096] It can be seen from the experiments of Example 11 and Example 12 above that the cellulose product prepared by dissolving the cellulose raw material with the green solvent provided by the present invention and further regenerating it has excellent performance. It should be particularly pointed out that based on the preparation method of the present invention, it can be seen that the green solvent provided by the present invention is directly mixed at room temperature, the steps are simple and the energy consumption is low, and the preparation conditions such as high temperature, high pressure, and nitrogen atmosphere in the prior art are not selected. The cellulose raw material can be further prepared by dissolving and regenerating the cellulose raw material with the green solvent provided by the present invention, and the cellulose product (such as regenerated cellulose film or regenerated cellulose fiber) can be prepared without depolymerizing the cellulose raw material and further preparing the depolymerization product through the depolymerization product.

[0097] The preferred embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations. However, these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a green solvent for dissolving cellulose, characterized in that: The preparation method comprises mixing a guanidine organic base with an acidic reagent to form a mixture, then stirring the mixture at room temperature until a homogeneous solution is formed, and then heating and drying the homogeneous solution to obtain a green solvent for dissolving cellulose.

2. The preparation method according to claim 1, characterized in that: The guanidine organic base is at least one selected from 1,1,3,3-tetramethylguanidine, tetraethylguanidine, tetrapropylguanidine, 2-tert-butyl-1,1,3,3-tetramethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, chlorphenguanidine, metformin, polyhexamethylene biguanide, diphenylguanidine, proguanil, and sulfaguanidine; Preferably, it is at least one of 1,1,3,3-tetramethylguanidine, 2-tert-butyl-1,1,3,3-tetramethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene.

3. The preparation method according to claim 1, characterized in that: The acidic reagent is a monoprotic acid or a diprotic acid.

4. The preparation method according to claim 3, characterized in that: The monoacid is selected from at least one of valeric acid, ethoxyacetic acid, 10-undecenoic acid, glycolic acid, aminoacetic acid, thioglycolic acid, formic acid, acetic acid, propionic acid, n-butyric acid, isobutyric acid, caproic acid, heptanoic acid, nonanoic acid, lauric acid, 3-mercaptopropionic acid, acrylic acid, lactic acid, pyruvic acid, 2-chloropropionic acid, 2-chloronicotinic acid, benzoic acid, p-hydroxybenzoic acid, phenylacrylic acid, α-methylacrylic acid, gluconic acid, cinnamic acid, alanine, leucine, isoleucine, valine, cystine, cysteine, methionine, threonine, serine, phenylalanine, tyrosine, tryptophan, proline, methionine, and hydroxyproline; More preferably, at least one of ethoxyacetic acid, formic acid, acetic acid, propionic acid, acrylic acid, and n-butyric acid; The dibasic acid is selected from at least one of oxalic acid, malonic acid, succinic acid, maleic acid, adipic acid, pimelic acid, azelaic acid, sebacic acid, isophthalic acid, terephthalic acid, glutamic acid, aspartic acid, malic acid and tartaric acid.

5. The preparation method according to claim 1, characterized in that: When the acidic reagent is a monobasic acid, the molar ratio of the guanidine organic base to the acidic reagent is (0.25-9):1; When the acidic reagent is a dibasic acid, the molar ratio of the guanidine organic base to the acidic reagent is (1-2):

1.

6. The preparation method according to claim 1, characterized in that: The conditions for stirring the mixture at room temperature include: a stirring speed of 500 rpm, a stirring time of 4-10 min, and preferably a stirring time of 5 min.

7. The preparation method according to claim 1, characterized in that: The conditions for heating and drying the homogeneous solution include: drying in a vacuum drying oven at a temperature of 90° C. for 6 hours.

8. A green solvent for dissolving cellulose prepared by the preparation method according to any one of claims 1 to 7.

9. The use of the green solvent in dissolving cellulose according to claim 7, characterized in that: The application comprises adding the cellulose raw material to be dissolved into the green solvent, heating and continuously stirring until the cellulose raw material is dissolved to obtain a cellulose solution.

10. The use of the green solvent in dissolving cellulose according to claim 9, characterized in that: The cellulose raw material is a mixture of one or more of wood dissolving pulp, cotton pulp, cotton linter pulp, wheat straw dissolving pulp, reed dissolving pulp, straw dissolving pulp, bamboo dissolving pulp and microcrystalline cellulose; Preferably, in the cellulose solution, the mass percentage of the cellulose raw material is 2-12%; Preferably, the heating temperature is 60-100°C, more preferably 80°C; Preferably, the stirring speed is 300 rpm; Preferably, the application further comprises recovering the solvent in the coagulation bath by rotary evaporation.